Peran Perilaku Organisasi dalam Membentuk Budaya Kerja - Purwanto, Eko; Siregar, Johannes Kristian; Meila, Kaca Dian; Zidan, Galuh Swayalu; Lesmana, Rudi; Muhlisin, Zihadi Dikri (Universitas Muhammadiyah Mataram, 2026)
Abstract: This study aims to analyze the role of organizational behavior in shaping the work culture at PT. Sunggong Logistics. The research focuses on leadership, communication, motivation, and group dynamics that influence the development of a healthy, productive, and results-oriented work environment. The research method employed is Community Service (PkM), which includes the following stages: problem identification, program planning, socialization, program implementation, monitoring and evaluation, and follow-up. Data were collected through observation, discussions, documentation, and direct surveys involving employees and management. The results indicate that positive organizational behavior, open communication, a combination of centralized and decentralized decision-making, as well as the implementation of Standard Operating Procedures (SOPs) and a reward system, contribute to building a collaborative, disciplined, and productive work culture. In conclusion, strengthening the values of professionalism, discipline, positive attitude, and spirituality among employees creates an adaptive and harmonious work environment that supports optimal organizational performance.Abstrak: Penelitian ini bertujuan untuk menganalisis peran perilaku organisasi dalam membentuk budaya kerja di PT. Sunggong Logistics. Fokus penelitian meliputi kepemimpinan, komunikasi, motivasi, dan dinamika kelompok yang memengaruhi terciptanya lingkungan kerja yang sehat, produktif, dan berorientasi hasil. Metode yang digunakan adalah Pengabdian kepada Masyarakat (PkM) dengan tahapan: identifikasi masalah, perencanaan program, sosialisasi, pelaksanaan program, monitoring dan evaluasi, serta tindak lanjut. Pengumpulan data dilakukan melalui observasi, diskusi, dokumentasi, dan survei langsung yang melibatkan karyawan dan manajemen. Hasil kegiatan menunjukkan bahwa penguatan perilaku organisasi melalui komunikasi terbuka, kombinasi pengambilan keputusan terpusat dan desentralisasi, penerapan Standar Operasional Prosedur (SOP), serta sistem penghargaan mampu membentuk budaya kerja yang kolaboratif, disiplin, dan produktif. Kesimpulannya, penguatan nilai profesionalisme, disiplin, sikap positif, dan spiritualitas karyawan dapat menciptakan lingkungan kerja yang adaptif dan harmonis, sehingga mendukung peningkatan kinerja organisasi secara optimal.